Prostate cancer risk stratification via eNose urine odor analysis: a preliminary report - Taverna, Gianluigi; Grizzi, Fabio; Bax, Carmen; Tidu, Lorenzo; Zanoni, Matteo; Vota, Paolo; Mazzieri, Cinzia; Clementi, Maria Chiara; Toia, Giovanni; Hegazi, Mohamed A. A. A.; Lotesoriere, Beatrice Julia; Hurle, Rodolfo; et al. (Frontiers in Oncology, 2024)
Introduction: Prostate cancer (PCa) is known for its highly diverse clinical behavior, ranging from low-risk, slow-growing tumors to aggressive and life-threatening forms. To avoid over-treatment of low-risk PCa patients, it would be very important prior to any therapeutic intervention to appropriately classify subjects based on tumor aggressiveness.Unfortunately, there is currently no reliable test available for this purpose. The aim of the present study was to evaluate the ability of risk stratification of PCa subjects using an electronic nose (eNose) detecting PCa-specific volatile organic compounds (VOCs) in urine samples.The study involved 120 participants who underwent diagnostic prostate biopsy followed by robot assisted radical prostatectomy (RARP). PCa risk was categorized as low, intermediate, or high based on the D'Amico risk classification and the pathological grade (PG) assessed after RARP. The eNose's ability to categorize subjects for PCa risk stratification was evaluated based on accuracy and recall metrics.The study population comprised 120 participants. When comparing eNose predictions with PG an accuracy of 79.2% (95%CI 70.8 -86%) was found, while an accuracy of 74.2% (95%CI 65.4 -81.7%) was found when compared to D'Amico risk classification system. Additionally, if compared low-versus -intermediate-/high-risk PCa, the eNose achieved an accuracy of 87.5% (95%CI 80.2-92.8%) based on PG or 90.8% (95%CI 84.2-95.3%) based on D'Amico risk classification. However, when using low-/-intermediate versus -high-risk PCa for PG, the accuracy was found to be 91.7% (95%CI 85.2-95.9%). Finally, an accuracy of 80.8% (95%CI72.6-87.4%) was found when compared with D'Amico risk classification.The findings of this study indicate that eNose may represent a valid alternative not only for early and noninvasive diagnosis of PCa, but also to categorize patients based on tumor aggressiveness. Further studies including a wider sample population will be necessary to confirm the potential clinical impact of this new technology.